KEEFEKTIFAN MODEL PEMBELAJARAN CLUSTERING DALAM KETERAMPILAN MENULIS PUISI SISWA KELAS V SD YAPIS 02 MANOKWARI - Zaki Mubarok; Syamsul Darmawan (Jurnal Muara Pendidikan, 2019)
This study aims to prove the effectiveness of the clustering learning model on poetry writing skills of fifth grade students of SD Yapis 02 Manokwari. This research is an experimental research involving one class. The population of this study was the fifth grade students of SD Yapis 02 Manokwari with 95 students spread into three classes. The sample chosen was the fifth grade students with 31 students. Sampling is done using the claster random sampling technique. Assessment instruments are used with instruments related to using the clustering learning model and the initial test (pretest) and the final test (posttest). The data obtained were analyzed using descriptive statistics and inferential statistics. The results of the descriptive statistics show that the effective clustering learning model for writing poetry skills in class V a Elementary School 02 Manokwari is evidenced by the value of the test taught using a clustering learning model in a good category with an average value of 83.6. The inferential statistical results of the calculation of the significance test for the t test are 4,440 > 1,690. This shows that the proposed hypothesis is accepted which means that the clustering learning model is effective against poetry writing skills carried out in class V of SD Yapis 02 Manokwari. Based on the presentation of the results of the data analysis and discussion, it can be concluded that the effectiveness of the clustering learning model for poetry writing skills of class V students of SD Yapis 02 Manokwari.